Model Means Ends Analysis Untuk Meningkatkan Motivasi Dan Hasil Belajar Matematika di Kelas IV SDI Al-Azhar 32 Padang - Nova Silvia; Firman Firman; Desyandri Desyandri (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2021)
This study aims to improve mathematics learning outcomes using the Means Ends Analysis (MEA) Learning Model in grade IV SDI Al-AZHAR 32 Padang. This research method is Classroom Action Research with collaborative techniques consisting of II cycles. The subjects of the research were fourth grade students of SDI Al-Azhar 32 Padang in the 2012/2013 school year. It can be concluded that learning mathematics using the Means Ends Analysis (MEA) Learning Model is proven to be able to improve learning outcomes in Mathematics in terms of Cognitive, Affective and Psychomotor fourth grade SDI Al-Azhar 32 Padang. The result of the average service for the class of Sioclus I was 60.00% then increased in the second cycle to be 83.50%